PELATIHAN PENGELOLAAN KEUANGAN DALAM MENUNJANG KEBERLANGSUNGAN USAHA NELAYAN: DI DESA KILANG - Yunita Leatemia, Senda; Wilhelmina Silooy, Revi; Boki, Emi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The lack of knowledge, literacy, and financial management practices of fishermen in the Refinery Village causes the financial recording system to be unstructured and often combines the use of money from sales with personal money, which ultimately has an impact on the sustainability of the business's financial performance to be unhealthy. In response to this situation, this community service activity aims to provide understanding and training to fishermen related to simple financial management with socialization, training, discussion and evaluation methods. The mechanisms used include mapping field problems, preparing training materials, implementing face-to-face activities with village partners, and evaluating participants' understanding. The results of the activity show that there is an increase in fishermen's understanding of good financial management methods for fishermen in the simple financial recording process, as well as the application of strategies in increasing income for the success of fishermen's businesses. In addition, this activity raised a commitment from participants and village partners to integrate financial recording practices into daily business activities. In the future, this program will be synergized with regular assistance as an effort to build economic independence of fishermen based on applicable financial literacy.